1999
DOI: 10.1046/j.1469-8137.1999.00446.x
|View full text |Cite
|
Sign up to set email alerts
|

The importance of xylem constraints in the distribution of conifer species

Abstract: Vulnerability of stem xylem to cavitation was measured in 10 species of conifers using high pressure air to induce xylem embolism. Mean values of air pressure required to induce a 50% loss in hydraulic conductivity (ϕ50) varied enormously between species, ranging from a maximum of 14.2±0.6 MPa (corresponding to a xylem water potential of −14.2 MPa) in the semi‐arid species Actinostrobus acuminatus to a minimum of 2.3±0.2 MPa in the rainforest species Dacrycarpus dacrydioides. Mean ϕ50 was significantly correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
120
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(129 citation statements)
references
References 40 publications
7
120
0
2
Order By: Relevance
“…In the context of our findings, range effects on speciation and extinction rates could explain contrasting diversities among podocarp lineages (see the electronic supplementary material, figure S3). Podocarps, in general, are strongly limited by drought [6,54] and in the Present, the majority of IL lineages is associated with high rainfall upper montane and alpine conditions, or they grow in high-latitude temperate rainforests as longlived pioneers or riparian species [55]. Such suitable environments are restricted in the Southern Hemisphere, as mesic temperate climates have contracted since the opening of the Southern Ocean from the Oligocene [56].…”
Section: Results and Discussion (A) Phylogeny And Divergence Timesmentioning
confidence: 99%
“…In the context of our findings, range effects on speciation and extinction rates could explain contrasting diversities among podocarp lineages (see the electronic supplementary material, figure S3). Podocarps, in general, are strongly limited by drought [6,54] and in the Present, the majority of IL lineages is associated with high rainfall upper montane and alpine conditions, or they grow in high-latitude temperate rainforests as longlived pioneers or riparian species [55]. Such suitable environments are restricted in the Southern Hemisphere, as mesic temperate climates have contracted since the opening of the Southern Ocean from the Oligocene [56].…”
Section: Results and Discussion (A) Phylogeny And Divergence Timesmentioning
confidence: 99%
“…However, the global data-basis used may not take into account local variations in soil water availability. A comparative ecophysiological study indicated that inter-specific variation in drought-induced xylem cavitation is often associated with differences in soil moisture availability [21].…”
Section: Relationships Between Vulnerability To Cavitation and Droughmentioning
confidence: 99%
“…duration of leaf growth [26]) besides stomatal conductance, net photosynthesis, and primary production. Even geographic distribution of woody species is considered to be associated with xylem hydraulic properties, and with xylem vulnerability to cavitation in particular [3]. At the same time, the relationships between leaf functioning within an individual crown and traits of the plant hydraulic architecture are still poorly understood [10,13].…”
Section: Introductionmentioning
confidence: 99%